Income, Saving Behavior, and Household Financial Decision-Making: A Moderated-Mediation Analysis of Behavioral and Economic Factors in Indonesia - Muhammad Sohilauw; Rosdiana Rosdiana; Andi Harmoko Arifin; Nasir Nasir; Muhammad Kafrawi Yunus (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose: This study examines the roles of income and saving behavior in household financial decision-making, with financial risk management as an intervening factor. Design/methodology/approach: This study uses survey data from 500 working individuals and applies a predictive composite modeling approach combining robust MM estimation and cross-validated regression to address non-normal behavioral finance data. Findings/Results: The results show that saving behavior has a strong positive effect on household financial decision-making and financial risk management. It also indirectly affects financial decision-making through financial risk management. Income has a positive but weaker effect. The interaction between income and saving behavior is significant, indicating that the effect of income becomes smaller when saving discipline is higher. The model explains 62.8% of the variance in household financial decision-making. Originality/Value: This study shows that household financial decisions are shaped not only by economic capacity but also by behavioral discipline. The findings suggest that strengthening saving behavior and financial risk management is more effective than relying on income alone.